Combined Toxicity Assessment of Chlorhexidine and Butyl Paraben on Daphnia Magna - Dharshini.P, Dharshini.P; Sakthi, D. Sri; Kishore Kumar, Meenakshi Sundaram; Martin, Taniya Mary (Journal of Neonatal Surgery, 2025)
Introduction:Water pollution from personal care products, including chlorhexidine (CHX) and butylparaben (BP), poses significant threats to aquatic ecosystems. While individual toxicities are well documented, their combined effects remain unclear. This research evaluates the individual and combined toxicity of CHX and BP on Daphnia magna. Using immobilization assays and Bliss independence analysis, the research investigates whether their interactions are additive, synergistic, or antagonistic, offering insight into the real-world risks these chemical mixtures pose to non-target aquatic organisms. Methodology:The immobilization of Daphnia magna was assessed at 24 and 48-hour intervals using five different concentrations of chlorhexidine and butyl paraben at varying ratios. Concentration ranges were selected based on environmental detection levels and established protocols for ecotoxicity testing. Each concentration was tested with 50 Daphnia magna (10 individuals per replicate). Toxicity levels were analyzed using the Bliss independence model, following OECD guidelines for Daphnia sp. Acute Immobilisation Test. Results:The individual toxicity of chlorhexidine at IC30, IC50, and IC70 were 27.47, 31.45, and 4.29 mg/L, respectively, while for butylparaben, the values were 11.59, 21.59, and 5.23 mg/L, respectively. The combination of chlorhexidine and butyl paraben at 2:1 ratio showed Combination Index (CI) of 2.45, 2.67 and 4.89 at IC30, IC50 and at IC70, respectively, indicating antagonistic interactions. Similar Antagonistic effects were observed at 3:1 ratio (the CI values at IC30, IC50 and IC70 were 2.9, 3.67, and 3.91) Conclusion:The findings reveal that CHX and BP interact antagonistically at both tested ratios, reducing overall toxicity compared to individual exposures. These results highlight the complexity of chemical interactions and the importance of incorporating mixture analysis into environmental risk assessments. Understanding such interactions is vital for accurately predicting ecological risks posed by contaminant mixtures in aquatic environments...